Pengaruh Kepuasan Kerja Terhadap Motivasi Kerja Perangkat Desa Se Kecamatan Pineleng - Devie S.R. Siwij (Peneliti.net, 2022)
The purpose of this research is to find out whether job satisfaction has an effect on the motivation of village employees in Pineleng Sub-district, Minahasa Regency, and to find out how much job satisfaction has an effect on work motivation in village staff in Pineleng District, Minahasa Regency. In this study, I use a quantitative research approach, which uses data that can be calculated to produce a strong quantitative interpretation, with the variables (X) “Job satisfaction” and (Y) “Employee Work Motivation” village officials in Pineleng District, Minahasa Regency. The results showed that 82.9.1 % Job Satisfaction (X) determines Work Motivation (Y) Pineleng Dua Indah Equipment, Pineleng District. Meanwhile, 17.1% of work motivation is influenced by other factors not examined. When viewed based on the research data obtained, it can be said that the Job Satisfaction of the Pineleng Dua Indah Village apparatus, Pineleng District is 55.78%, which means that the implementation has not been maximized. This shows that there are 43.22% of current work motivation is not derived from job satisfaction. The lack of job satisfaction of the Pineleng Dua Indah village apparatus is more triggered by the lack of appreciation for the work felt by the village apparatus. Work Motivation of Pinelang Dua Indah Village Staff is 61.01% or in other words there are 39.91% of village officials still lacking motivation.